Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/la4004406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer-Graft Modification on the Order Formation in Particle Assembly Structures

Abstract: The propensity of particle brush materials to form long-ranged ordered assembly structures is shown to sensitively depend on the brush architecture (i.e., the particle radius as well as molecular weight and grafting density of surface-bound chains). In the limit of stretched chain conformations of surface-grafted chains the formation of regular particle array structures is observed and interpreted as a consequence of hard-sphere-type interactions between polymer-grafted particles. As the degree of polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 27 publications
(62 reference statements)
5
107
0
Order By: Relevance
“…The reported N c values correspond to the transition pint between the two regimes. For more details on the experimental procedure (as well as data) the reader is referred to reference …”
Section: Resultsmentioning
confidence: 99%
“…The reported N c values correspond to the transition pint between the two regimes. For more details on the experimental procedure (as well as data) the reader is referred to reference …”
Section: Resultsmentioning
confidence: 99%
“…Hairy NPs were synthesized via a grafting from the SiO 2 surface providing aHNP systems with varying graft density and polymer molecular weight (Table ). The silica particles were obtained from Nissan and are ∼16 nm (polydispersity of 35%).…”
Section: Methodsmentioning
confidence: 99%
“…The latter is an important prerequisite to understand the role of polymer-graft modification on the interaction and structure formation characteristics of particle brushes in solid film assemblies. Choi et al (2010Choi et al ( , 2013 synthesized and characterized a number of polymergrafted nanoparticles (silica coated with polystyrene and poly methyl methacrylate) using the criteria given by Ohno et al It was found that the ability of these particles to form long-range ordered structures depended sensitively on the polymer brush architecture. In the limit of high grafting density and stretched chain conformations, particle array structures, which resembled close-packed hard-sphere arrays, were observed.…”
Section: Role Of Polymer-graft Modification On the Interaction Dynammentioning
confidence: 99%